Measuring empowerment of women and girls - Some thoughts on the 'what' and the 'how' - Eerdewijk, Anouka van; Newton, Julie (CGIAR Collaborative Platform on Gender Research, 2018)
Presented by Anouka van Eerdewijk and Julie Newton (KIT) on 31 January 2018, as part of the webinar 'Measuring empowerment of women and girls – the what and the how'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and KIT Royal Tropical Institute.